2018
DOI: 10.2217/nnm-2018-0180
|View full text |Cite
|
Sign up to set email alerts
|

AS1411 aptamer-targeted Gold Nanoclusters Effect on the Enhancement of Radiation Therapy Efficacy in Breast tumor-bearing Mice

Abstract: Aim: Herein, the AS1411 aptamer-targeted ultrasmall gold nanoclusters (GNCs) were assessed at different aspects as a radiosensitizer. Materials & methods: AS1411 aptamer-conjugated gold nanoclusters (Apt–GNCs) efficacy was evaluated at cancer cells targeting, radiosensitizing effect, tumor targeting, and biocompatibility in breast tumor-bearing mice. Results: Flow cytometry and fluorescence microscopy exhibited more cellular uptake for Apt–GNCs in comparison with GNCs. In addition, inductively coupled plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 49 publications
0
52
0
Order By: Relevance
“…A gold nanocluster conjugate of the AS1411 aptamer enhanced the efficacy of radiation therapy in breast tumor-bearing mice. Importantly, the authors reported a specific enrichment of the radiosensitizing gold nanoclusters in the breast tumors and a significant increase in the mean survival times of the animals [75]. Analogously, the combination of silver nanoparticles with polyethylene glycol (PEG)-functionalized AS1411 aptamer improved the outcome of radiation therapy in preclinical glioma models.…”
Section: Aptamers With Metal (Nano-)formulationsmentioning
confidence: 97%
“…A gold nanocluster conjugate of the AS1411 aptamer enhanced the efficacy of radiation therapy in breast tumor-bearing mice. Importantly, the authors reported a specific enrichment of the radiosensitizing gold nanoclusters in the breast tumors and a significant increase in the mean survival times of the animals [75]. Analogously, the combination of silver nanoparticles with polyethylene glycol (PEG)-functionalized AS1411 aptamer improved the outcome of radiation therapy in preclinical glioma models.…”
Section: Aptamers With Metal (Nano-)formulationsmentioning
confidence: 97%
“…Aptamer-based nanostructures have also been widely used in medicine, biology, and nanoelectronics due to the high stability, as shown in Table 1. The AS1411 aptamer conjugated with gold nanoclusters was tested in mice cancer cells and demonstrated to be a good radiosensitizer (Ghahremani et al 2018). Through cell-SELEX, the JHIT2 aptamer was selected and labeled with FAM and iodine-131 to detect human hepatoma cell line HepG2 by a fluorescent signal (Zhang et al 2020).…”
Section: Aptamers Applicationsmentioning
confidence: 99%
“…In another study, he has introduced SPIONs conjugated J591 Mab and their experiments confirmed the high potential of the nanoprobe as a specific MRI contrast agent for the detection of PSMA-expressing prostate cancer. [36]…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Due to extensive applications of magnetic iron oxide nanoparticles in biomedicine, many studies were performed under in vitro conditions and their cytotoxicity was investigated. [536] In this way, Keshtkar et al . [5] prepared a novel aptamer-conjugated nanoparticle using AS1411 aptamer which was conjugated to Fe 3 O 4 @Au nanoparticles on mouse mammary carcinoma (4T1) cells that overexpressed nucleolin.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%